Modelo de gestión de talento humano para elevar el desempeño laboral de la empresa Ingemed ubicada en Guajalo cantón Quito en el período 2015-2016 - Guaigua Quillupangui, Jessica Maribel (2016)
This project aims to develop a Management Model of Human Talent to raise the job performance of the company Ingemed S.A located in Guajalo canton Quito in the period 2015-2016, that allow enhance continuously the intellectual capacity of the employees to improve of personnel management with the purpose of organizing the processes of management and coordinate the activities. Also, is identified the variables that involving the investigation to develop the theoretical framework therefore, it has been made the analysis and diagnostic situational of all the functions that performance in the company Ingemed S.A with the use of the methodology of the investigation in where is applied the techniques and instruments necessary through which is managed to gather information enough about of the real situation of the organization….